A compatible model of family medicine residency training in Iran. Issue 4 (13th January 2021) - Khatami, Farnaz; Shariati, Mohammad; Motezarre, Asiyeh
Abstract : Purpose: One of the major challenges in practicing family medicine residents (FMRs) is the choice of an appropriate pattern in training health centers (THCs) to provide high-quality health services to patients. This study aimed to design an efficient residency training model in Iranian healthcare centers. Design/methodology/approach: A four-phase qualitative study with the nominal group technique was carried out in 2018–2019. The required standards of THCs and superior educational practices were initially extracted from the review literature. After collecting and presenting the key findings to the experts' panel, the required training standards and the optimal strategic model to educate FMRs in THCs were prioritized by a nine-point rating system for the well-structured terms of indigenous resources. Findings: Twenty-two educational standards for FMRs in THCs were finalized after reviewing the literature and taking an opinion poll of experts. The highest assessment scores belonged to sufficient numbers of referrals for common health issues and the existence of satisfactory educational and recreational facilities in THCs. The problem-based (PBL), task-based (TBL) and context-based (CBL) learning models were better strategies than guided-discovery learning (GDL) and small group teaching (SGT) ones to train FMRs in THCs. Also, PBL and SGT models were rated as the best and worst advanced medical education methods to empower FMRs. Originality/value: Due to different resources available in THCs and training centers, different factors and infrastructures should be considered to meet the required standards in building the integrative training model for FMRs in THCs.